Food deprivation increases hepatic hepcidin expression and can overcome the effect of Hfe deletion in male mice. Issue 11 (25th May 2018) - Mirciov, Cornel S. G.; Wilkins, Sarah J.; Anderson, Gregory J.; Frazer, David M.
ABSTRACT: Iron‐loading disorders, such as hereditary hemochromatosis, are associated with inappropriately low expression of the iron regulatory hormone, hepcidin. A recent study has demonstrated that food deprivation can increase hepcidin production in mice. We have examined this effect in more detail to determine whether the pathway(s) that are responsible might provide novel targets for pharmaceutical intervention in disorders of iron homeostasis. C57BL/6 mice were deprived of food for 5, 10, 16, or 24 h before euthanasia, then blood and tissue samples were collected for analysis. The effect of food deprivation was also examined in Hfe −/− mice, a model of hereditary hemochromatosis, as well as mice that were maintained on an iron‐deficient diet or injected with erythropoietin. Food deprivation increased the hepatic expression of the gene that encodes hepcidin, hepcidin antimicrobial peptide 1 (Hamp1), with maximal expression observed after 16 h, and was able to overcome the reduction in Hamp1 expression associated with Hfe deficiency. Food deprivation also increased Hamp1 expression in response to stimuli that more strongly suppress the gene, such as iron deficiency and erythropoietin treatment, but the effects were not significant. These results indicate that Hamp1 induction by food deprivation is independent of HFE and suggest that targeting the pathway regulated by food deprivation could have clinical benefit in iron loading conditions.—Mirciov, C. S. G., Wilkins, S. J., Anderson, G. J., Frazer, D. M. Food deprivation increases hepatic hepcidin expression and can overcome the effect of Hfe deletion in male mice. FASEB J. 32, 6079–6088 (2018). www.fasebj.org